Characterisation of the unique large Armadillo repeat protein (LARP) in the malaria parasite Plasmodium berghei - Stock, Jessica (2016)
The family of Armadillo(ARM) repeat proteins is known to play key roles in the cellular machinery of eukaryotic cells, including processes like gene expression, cell signalling and cytoskeletal organisation. Their repeating 42 amino acid motif provides a platform for numerous protein-protein interactions. Despite their known importance in eukaryotic cells, ARM repeat proteins remain poorly investigated in Apicomplexan parasites, including the malaria causing Plasmodium species. This study characterises the phylum-specific large Armadillo repeat protein (LARP), one of the 10 ARM repeat proteins known in Apicomplexa. For the first time, the localisation of a fluorescent tagged LARP protein was determined in the rodent malaria model system Plasmodium berghei. Live cell imaging revealed a predominant cytosolic expression of the protein in every life cycle stage of the parasite. The invasive P. berghei stages additionally demonstrate a distinct apical localisation of LARP-GFP, that forms a ring-like structure at the apical end of the cell. Subcellular fractionation assays confirmed the cytosolic expression, but also indicated a partial membrane attachment of LARP, that is possibly enabled through post-translational methylation. The apical expression and membrane attachment of LARP-GFP strongly suggest a localisation of LARP to the apical complex and therefore a connection to the invasion and motility machinery of P. berghei. A functional analysis indicated that LARP is likely essential in the asexual blood stages. Despite different approaches in this study, a comprehensive functional analysis through a conditional knockdown system has not yet been achieved. However, the presence of LARP in every P. berghei life cycle stage, its distinct properties in invasive parasite stages and apicomplexan-specific nature suggest LARP as a possibly interesting drug-target and highlight the overall importance of ARM repeat proteins in Plasmodium.